Materials Processing Fundamentals 2018 (The Minerals, Metals & Materials Series, 2018)
This book includes contributions from the Materials Processing Fundamentals Symposium held at the TMS 2018 Annual Meeting & Exhibition in Phoenix, Arizona. Covering the physical and numerical modeling of materials processing, the volume covers a range of metals and minerals. Authors present models and results related the basics of processing such as extraction, joining, separation, and casting. The corresponding fundamentals of mass and heat transport as well as physical and thermodynamics properties are addressed, allowing for a cross-disciplinary vision of the field.